2020
DOI: 10.14260/jemds/2020/169
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Single Point and Two Point Technique for Ultrasound Guided Supraclavicular Brachial Plexus Block in Patients Undergoing Elbow, Forearm and Wrist Surgeries- A Prospective Observational Study

Abstract: BACKGROUNDUse of ultrasound for brachial plexus block has improved the precision of drug deposition around the plexus and hence the quality of the block. But there has been debate whether single point technique or double point technique is superior. Our aim was to compare the two techniques for the onset, completeness and quality of the block. METHODSA prospective observational study was designed. 140 patients were equally divided into Group A and Group B containing 70 posted for elbow, forearm and wrist surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…[ 9 ], Pratap et al [ 12 ], Tran et al [ 13 ], and Arab et al [ 11 ] also observed that the single-point injection technique takes lesser procedure time. Choudhary et al [ 2 ], Jung et al [ 10 ], Murali et al [ 14 ], Tran et al [ 13 ], Pratap et al [ 12 ], Sherin et al [ 15 ], Arab et al [ 11 ], and Vallapureddy et al [ 9 ] all found delayed sensory and motor onset in the single-point injection group, compared to double- or triple-injection groups.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ], Pratap et al [ 12 ], Tran et al [ 13 ], and Arab et al [ 11 ] also observed that the single-point injection technique takes lesser procedure time. Choudhary et al [ 2 ], Jung et al [ 10 ], Murali et al [ 14 ], Tran et al [ 13 ], Pratap et al [ 12 ], Sherin et al [ 15 ], Arab et al [ 11 ], and Vallapureddy et al [ 9 ] all found delayed sensory and motor onset in the single-point injection group, compared to double- or triple-injection groups.…”
Section: Discussionmentioning
confidence: 99%